Fitorremediação de solo contaminado com 2,4-D + picloram na Amazônia Oriental - SILVA, Jéssica Paloma Pinheiro da (2017)
The herbicides have a residual effect and have a number of modifications to the environment. To address a soil contamination by composite xenobiotics, one of the facilities used and a phytoremediation, which uses plants for extraction / softening of the pollutant compound. The objective of this work was to evaluate the potential of Braquiarão grass and Mombaça grass in phytoremediate soil treated with herbicide 2,4-D + picloram, using radish as a bioindicator plant. The experiment was conducted in a greenhouse in a completely randomized design in two stages. In the first stage the treatments were composed by Brachiarão grass cultivation and Mombaça grass cultivation treated with and without the herbicide dose, with five replications each treatment. In the second stage, the treatments consisted of radish Crimson Giant cultivation in: soil free of herbicide residue; soil contaminated with previous cultivation of the Brachiarão grass species; soil contaminated with previous cultivation of the Mombaça grass specie; and contaminated soil without the previous cultivation of grass, with five replications each treatment. Vessels with 8 dm³ and without holes were used, which were treated with 2,4-D + picloram herbicide, individually on the surface of each pot, in pre-emergence, 15 days after application the grasses were sown. At 50 days after sowing (DAS), the forages were harvested and their phytoremediation potential was evaluated. These were segregated in part area and root, analyzing the parameters of fresh biomass (g), dry biomass (g) and height (cm) of the segregated parts for each treatment. After the phytoremediation plants were removed, the radish was transplanted in each vessel. At 5, 10, 15 and 20 days after emergence (DAE) the visual phytotoxicity of the plants was evaluated and at 20 DAE was determined the accumulation of green and dry matter (g), plant height (cm), analyzes were using the same forage analysis procedure. The results showed that the evaluated grasses present phytoremediation characteristics for auxinic herbicides; the radish can be used as a bioindicator of the presence of herbicide 2,4-D + picloram; the period evaluated was not sufficient for the total withdrawal of the effects of the herbicide, being necessary continuity of the phytoremediation process.